Social entrepreneurship and employment challenges of persons with mental disabilities - Anca, Evija; Sloka, Biruta (University of Latvia, 2020)
In developed countries there is a valuable experience how to include people with disabilities into society: involve in several activities and let them know as people valuable for the society. More and more academic research is devoted to those aspects as well as public policy is developed to create and support social entrepreneurship. Aim of the paper is to analyse findings and good practice of employment of people with mental disabilities in several countries and analyse the situation and possible developments on employment of people with mental disabilities in Latvia. Tasks of research: 1) analyse results of academic findings on good practice and challenges in employment of people with mental disabilities wold-wide; 2) analyse the developments and trends on employment of people with mental disabilities in Latvia; 3) propose possible development scenarios on employment of people with mental disabilities in Latvia. Research methods used in research: scientific publications analysis; analysis of legislative documents on employment of people with mental disabilities, analysis of statistical data on employment of people with mental disabilities. Research results have shown that in recent years many important steps in employment of people with mental disabilities in Latvia has been reached but there are some difficulties in realise of sustainability in this aspect.
Keywords: social entrepreneurship; disability; communities; job security; market integration; social exclusion; Research Subject Categories::SOCIAL SCIENCES::Business and economics